Enhancing the Learning Outcomes of Automotive Electrical Wiring Diagram through Android Simulation – A Conceptual Design for Automotive Vocational School - Mubarak, Ibnu; Warju, Warju; Danur Isnantyo, Fajar; Nurtanto, Muhammad; Rahman, Reza A.; Suyitno, Suyitno (International Journal of Psychosocial Rehabilitation, 2020)
The implementation of technology in the learning process must be implemented as a real effort to improve the quality of education in the industrial era 4.0. Technology can be utilized to achieve adequate learning outcomes that conform to the student’s characteristics at present. This article discusses the application of technology in the learning process for an automotive vocational school. The designed application is a game-based challenge which able to installed either in a mobile telephone or computer for learning the automotive electrical wiring diagram. As technology develops in vehicles that utilize a lot of electrical and computer systems, thus the outcomes in automotive vocational schools must be adjusted to real conditions in the field. The automotive electrical system is an essential lesson for automotive vocational education, and it requires a depth understanding of the student, which trains the student’s high order thinking skills. In order to maximize the learning process, the authors and teams design a game-based application on a mobile phone for the automotive electrical wiring diagram course. The application was developed according to the current student’s characteristics which familiar with the mobile phone. The goals of the concept are to improve the learning process and ease of use for teachers and students during the class activities. The application is designed based on the automotive electrical wiring standard. After the initial test, the authors and teams found this concept can attract students' interest in learning the automotive electrical system even though the topic is considered as difficult level (High Order Thinking) and gives positive results in achieving the target of learning outcomes.